Survival under dictatorships : life and death in Nazi and communist regimes - Borhi, László 1961- (Central European University Press, 2024)
A complex array of individual responses to the abuse of power by the state is represented in this book in three horrific episodes in the history of East-Central Europe. The three events followed each other within a span of about ten years: the deportation and murder of Hungarian Jews in Nazi death and labor camps; the Arrow Cross terrorist rule in Budapest; and finally the Stalinist terror in Hungary and East-Central Europe. Through the prism of survival, László Borhi explores the relationship between the individual and power, attempting to understand the mechanism of oppression and terror produced by arbitrary, unbridled power through the experience of normal people. Despite the obvious peculiarities of time and place, the Hungarian cases convey universal lessons about the Holocaust, Nazism, and Stalinism. In the author's conception, the National Socialist and Stalinist experiences are linked on several levels. Both regimes defended their visions of the future against social groups whom they saw as implacable enemies of those visions, and who therefore had to be destroyed for sake of social perfection. Furthermore, the social practices of National Socialism were passed on. And although Stalinism was imposed by a foreign power, some of the survival skills for coping with it were rehearsed under the previous hellish experience.